Faktor-Faktor Yang Mempengaruhi Kinerja Sistem Informasi Akuntansi Pada Lembaga Perkreditan Desa (LPD) Do Kecamatan Kubu: Keterlibatan Pengguna, Kemampuan Teknik Personak, Ukuran Organisasi, Program Pendidikan dan Pelatihan Pengguna - Yunita, Eka; Herawati, Nyoman Trisna (Vokasi : Jurnal Riset Akuntansi, 2023)
Accounting information systems are computer-based systems where there is interaction between human resources as implementers and machines as tools to process and convert financial data and other data into information needed by management to plan, control, and operate a business. Accounting Information Systems have a very important role, especially in LPD, but where accounting information system users who work at LPD in Kubu sub-districts still feel confused in operating or carrying out their duties and jobs using existing accounting information systems. This study aims to examine the effect of user involvement, personal technical capabilities, organizational size, user education and training programs, on the Performance of Accounting Information Systems. The type of research conducted is a quantitative approach and causal research design. The subjects of this study were employees of LPD Kubu District, with certain criteria. The object of study includes user involvement, personal engineering capabilities, organizational size, user education and training programs. Researchers used purposive sampling techniques to determine a sample of 60 respondents. Data was collected through questionnaires using Likert scale. The data were analyzed using multiple linear regression. The results showed that there was a significant influence of user involvement, personal technical capabilities, organizational size, user education and training programs, stimulated on the performance of accounting information systems.